Safety, feasibility and initial efficacy of an app-facilitated telerehabilitation (AFTER) programme for COVID-19 survivors: a pilot randomised study - Kristine M Erlandson; Jacob John Capin; Amy Nordon-Craft; Sarah E Jolley; Jennifer E Stevens-Lapsley; Mary Morrow; Meghan Connors; Kristine Hare; Samantha MaWhinney; Michelle Rauzi; Sheryl Flynn (BMJ Open)
Objectives Determine the safety, feasibility and initial efficacy of a multicomponent telerehabilitation programme for COVID-19 survivors.Design Pilot randomised feasibility study.Setting In-home telerehabilitation.Participants 44 participants (21 female, mean age 52 years) discharged home following hospitalisation with COVID-19 (with and without intensive care unit (ICU) stay).Interventions Participants were block randomised 2:1 to receive 12 individual biobehaviourally informed, app-facilitated, multicomponent telerehabilitation sessions with a licenced physical therapist (n=29) or to a control group (n=15) consisting of education on exercise and COVID-19 recovery trajectory, physical activity and vitals monitoring, and weekly check-ins with study staff. Interventions were 100% remote and occurred over 12 weeks.Primary and secondary outcome measures The primary outcome was feasibility, including safety and session adherence. Secondary outcomes included preliminary efficacy outcomes including tests of function and balance; patient-reported outcome measures; a cognitive assessment; and average daily step count. The 30 s chair stand test was the main secondary (efficacy) outcome.Results No adverse events (AEs) occurred during testing or in telerehabilitation sessions; 38% (11/29) of the intervention group compared with 60% (9/15) of the control group experienced an AE (p=0.21), most of which were minor, over the course of the 12-week study. 27 of 29 participants (93%; 95% CI 77% to 99%) receiving the intervention attended ≥75% of sessions. Both groups demonstrated clinically meaningful improvement in secondary outcomes with no statistically significant differences between groups.Conclusion Fully remote telerehabilitation was safe, feasible, had high adherence for COVID-19 recovery, and may apply to other medically complex patients including those with barriers to access care. This pilot study was designed to evaluate feasibility; further efficacy evaluation is needed.Trial registration number NCT04663945.